Earth Observation with SAR Satellite Formations: New Techniques and Innovative Products - Krieger, Gerhard; Fiedler, Hauke; Moreira, Alberto (2009)
This paper discusses the use of small satellites for future radar remote sensing applications. After a short introduction, we give first an overview of the TanDEM-X mission to be launched in autumn 2009. Here, special emphasis is put on the demonstration of innovative synthetic aperture radar (SAR) imaging techniques. Then, novel SAR configurations are introduced which make synergistic use of multiple small satellites flying in close formation. Performance examples demonstrate their unique capabilities for advanced Earth observation applications. Among these opportunities are the generation of digital elevation models with decimetre accuracy, the monitoring of ocean currents, and the measurement of small vertical displacements from snow accumulation, vegetation growth, and thawing permafrost soils. Challenges associated with the use of small satellites are pointed out and solutions to overcome them are presented.